Fourier-transform Infrared (FTIR) Characterization and Radical Scavenging Activity Ziziphus spina-christi (Rhamnaceae) Rootbark Fractions - Dahiru, Mubarak Muhammad; Hauwa, Alkasim Yahaya; Zainab, Muhammad; Pius, Pwadumadi; Yakubu, Nuhu Dangana (Majalah Obat Tradisional, 2025)
This study focused on the secondary metabolite characterization and radical scavenging activity of the chloroform (CF), ethyl acetate (EF), and aqueous fractions (AF) of Ziziphus spina-christi to ascertain its therapeutic potential against oxidative stress. Fourier-transform infrared (FTIR) characterization and determination of in vitro radical scavenging activity of the plant were carried out. Alkaloids, saponins, and flavonoids were present in all the fractions with steroids absent in the AF. The FTIR characterization detected alcohol, conjugated alkenes, and amine groups in the CF and EF. However, alkanes, aromatic amines, sulfonates, and monosubstituted alkanes were also detected in the latter. Moreover, carboxylic acid, alkane, alkene, amines, and phenols were identified in the AF. The EF (72.46 ± 0.55 µg/ml AAE) and AF (71.51± 0.46 µg/ml AAE) demonstrated a significantly (p < 0.05) higher total antioxidant capacity (TAC) than CF (50.33 ±0.27 µg/ml AAE). The AF (54.07 ± 0.97 µg/ml AAE) exhibited a significantly (p < 0.05) higher total reducing power (TRP) than the EF (42.76 ± 1.60 µg/ml AAE) and CF (30.13 ± 1.32 µg/ml AAE). A significantly (p < 0.05) higher percentage of lipid peroxidation inhibition was exhibited by the CF (71.25% ±3.41) compared to the EF (54.17% ±2.66). Moreover, all the fractions showed significantly (p < 0.05) higher inhibition than ascorbic acid (18.33% ±1.56). The CF (0.16 ±0.01 nmol/ml) and EF (0.21 ±0.01 nmol/ml) demonstrated a significantly (p < 0.05) lower MDA concentration than the AF (0.42 ±0.01 nmol/ml) and ascorbic acid (0.38 ±0.02 nmol/ml). Conclusively, the Z. spina rootbark has potential antioxidant application in oxidative stress therapy with a focus on anti-lipid peroxidation for the CF though the AF has better TAC and TRP.